ACUTE MYOCARDITIS LINKED TO THE ADMINISTRATION OF THE COVID 19 VACCINE - Burkhanova Dilovar Sadridinovna; Kudratova Zebo Erkinovna; Хudaykulova Malika Bahodirovna; Rahimova Gulchiroy Olim qizi (Journal of new century innovations, 2023)
Abstract. Myocarditis is a broad term that refers to a range of immunological processes that can damage the function and structure of the myocardium. Viruses cause most myocarditis cases. Cause-effect. Myocarditis caused by non-infectious agents is uncommon, it’s linked to systemic inflammatory illnesses, medications, and immunizations. COVID-19 vaccines usually cause minor side effects. which may become more severe with the second dosage, though more serious adverse effects have been documented. Troponin levels in the lab were high, and viral serologists were negative. In spite of our findings, it seems that having COVID-19 infection is linked to a much greater chance of cardiac involvement than having COVID-19 immunization.